An exact solution of boundary-value problem - Khoma, N. H. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish conditions under which the problem u_tt — u_xx = f(x, t), u(x, 0) = u(x, π) = 0 possesses the classical solution.